2013
DOI: 10.1007/978-3-642-39405-8_32
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Models of Decision Making Processes for Human-Robot Interaction

Abstract: A fundamental aspect of human-robot interaction is the ability to generate expectations for the decisions of one's teammate(s) in order to coordinate plans of actions. Cognitive models provide a promising approach by allowing both a robot to model a human teammate's decision process as well as by modeling the process through which a human develops expectations regarding its robot partner's actions. We describe a general cognitive model developed using the ACT-R cognitive architecture that can apply to any situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 7 publications
(5 reference statements)
0
14
0
Order By: Relevance
“…Others suggest developing (Neerincx, de Greef, Smets, & Sam, 2011; Ososky et al, 2012) or have developed simulated robotic SMMs (Kennedy & Trafton, 2007) but do not provide comprehensive frameworks for realizing robot SMMs. It is suggested that SMMs are necessary to make the robots true teammates (Ososky et al, 2012), and ACT-R (adaptive control of thought–rational) was used to demonstrate, in simulation, the use of mental models to improve performance (Libiere, Jentsch, & Ososky, 2013), although no comprehensive framework was provided for integrating SMMs into robots that can function in uncertain and dynamic environments.…”
Section: A Brief Overview Of Smmsmentioning
confidence: 99%
“…Others suggest developing (Neerincx, de Greef, Smets, & Sam, 2011; Ososky et al, 2012) or have developed simulated robotic SMMs (Kennedy & Trafton, 2007) but do not provide comprehensive frameworks for realizing robot SMMs. It is suggested that SMMs are necessary to make the robots true teammates (Ososky et al, 2012), and ACT-R (adaptive control of thought–rational) was used to demonstrate, in simulation, the use of mental models to improve performance (Libiere, Jentsch, & Ososky, 2013), although no comprehensive framework was provided for integrating SMMs into robots that can function in uncertain and dynamic environments.…”
Section: A Brief Overview Of Smmsmentioning
confidence: 99%
“…ACT-R is a theory of cognition that involves the integration of multiple information processing modules (e.g., declarative memory, perceptual-motor) to produce a holistic representation of human cognition (Anderson, Bothell, Byrne, Douglass, Lebiere, & Qin, 2004). Details of the computational decisionmaking model, and a preliminary report on model training using data from expert decision makers, can be found in Lebiere, Jentsch, and Ososky (2013). The current paper reports on an extension of the project reported in Lebiere et al (2013).…”
Section: Research Backgroundmentioning
confidence: 99%
“…Details of the computational decisionmaking model, and a preliminary report on model training using data from expert decision makers, can be found in Lebiere, Jentsch, and Ososky (2013). The current paper reports on an extension of the project reported in Lebiere et al (2013). The goal of the extended research project was to validate the ACT-R model against the responses of novice human participants.…”
Section: Research Backgroundmentioning
confidence: 99%
See 2 more Smart Citations